Um estudo exploratório sobre a Employee Value Proposition (EVP) no mercado de seguros brasileiro - Vergara, Rogério Guede (2016)
Human resource management practices follow the evolution in the management of the human capital of organizations. Marketing activities focused on corporate brand providing essential and strategic service to identify, formatting and dissemination of the employer's brand. Together the two areas begin to play supportive role in attracting qualified professionals enhancing and propagating the corporate identity to potential candidates through EVP. The EVP, the Employer Brand and Employer Reputation relate through the practices of recruitment and selection, which is HR area to first keep in touch with potential candidates and start the construction of the psychological contract with the new employee. The employer brand, as the image of the organization, is used to attract, retain and engage people and has the EVP as its central core. This study identifies the practice of recruitment and selection as the main theoretical connection between EVP, the employer brand and employer reputation and identifies that Opportunity as the most relevant dimension of the EVP for the studied public.